The Disability’s Perception In The Sexuality’s Need And Reproductive Health In Yogyakarta 2019 – A Scoping Review - Youlenta Ernes Sontha (International Journal of Health Science and Technology, 2021)
Background: Disable people are all people who experience physical, intellectual, mental and sensory limitations in the long term that inhibit and make them difficult to interact with the environment and/to participate fully and effectively with other citizens based on equal rights. Purpose: This study aims for mapping the literature, exploring information about research activities related to the topic being investigated and also investigating problems or gaps in the research area to be investigated. Method: The applied approach to review the literature was Arksey dan O’Malley framework. The applied framework to manage research questions was PEOS so the strategy of searching used 3 databases namely Science direct, Pubmed, and Whiley with the identification of relevant studies to the inclusion and exclusion. Result: Disable people are human beings who can feel the biological needs. Negative views from family, health workers, and parents as well are the obstacles for people with disabilities who should get special attention. They requires more specific information and implementation on sexual and reproductive health for disable people. The limited access or sexual and reproductive health services by PWPD in Kampala was caused by some challenging conditions like limited access of  information accepted so that they lack of understanding of biological needs  they should obtain.Keywords: disability, sexuality and reproductive health